I Codici Etiopici del Fondo Martini nella Biblioteca Forteguerriana di Pistoia - Lusini, Gianfrancesco (Aethiopica, 2002)
In the Biblioteca Forteguerriana of Pistoia (Italy), a small collection of Ethiopian manuscripts is kept, entrusted to the Library by the heirs of Ferdinando Martini (1841-1928), “governatore civile” of the Colonia Eritrea from 1897 to 1907. These five manuscripts are catalogued here. Of great philological and artistic relevance is the illustrated Octateuch dated 1438 (Ms. Martini etiop. n. 2 = Zanutto n. 5), probably written in Tigrāy, namely in the monastery of Dabra Seqwert, district of Saḥart. In the XIXth-cent. chronological codex Martini etiop. n. 1 (= Zanutto n. 1), the materials transmitted by the traditional Liber Axumae are considerably enlarged and updated. The homiletic volume Martini etiop. n. 5 (= Zanutto n. 2), previously owned by Eǧǧegāyyahu, the mother of Menilek II (1844–1913), Emperor from 1889 to 1913, dates back to the XIXth cent. and contains various texts, still unpublished. The collection includes also an XVIIIth-cent. Hāymānota ’abaw (Ms. Martini etiop. n. 4 = Zanutto n. 4), closing with the apocryphal Book of the Letter, and a XVII–XVIIIth-cent. History of the Galla (Ms. Martini etiop. n. 3 = Zanutto n. 3), possibly the oldest manuscript of one of the first works of Amharic literature.